Systemic administration of valproic acid and zonisamide promotes differentiation of induced pluripotent stem cell–derived dopaminergic neurons - Yoshikawa, Tatsuya; Samata, Bumpei; Ogura, Aya; Miyamoto, Susumu; Takahashi, Jun (Frontiers in Cellular Neuroscience, 2013)
Cell replacement therapy using embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) is a promising strategy for the treatment of neurologic diseases such as Parkinson’s disease (PD). However, a limiting factor for effective cell transplantation is the low survival rate of grafted cells, especially neurons. In this study, we modified the host environment and investigated whether the simultaneous administration of soluble factors can improve the survival and differentiation of murine iPSC-derived dopaminergic (DA) neurons in host brains. With the goal of applying this technology in clinical settings in the near future, we selected drugs that were already approved for clinical use. The drugs included two commonly used anticonvulsants, valproic acid (VPA) and zonisamide (ZNS), and estradiol (E2), also known as biologically active estrogen. Following neural induction of murine iPSCs, we collected neural progenitor cells by sorting PSA-NCAM+ cells, then treated the PSA-NCAM+ cells with drugs for four days. An immunofluorescence study revealed that 0.01 mM and 0.1 mM of VPA and 10 nM of E2 increased the percentage of tyrosine hydroxylase+ (TH: a DA neuron marker) cells in vitro. Furthermore, 0.1 mM of VPA increased the percentage of TH+ cells that simultaneously express the midbrain markers FOXA2 and NURR1. Next, in order to determine the effects of the drugs in vivo, the iPSC-derived NPCs were transplanted into the striata of intact SD rats. The animals received intraperitoneal injections of one of the drugs for four weeks, then were subjected to an immunofluorescence study. VPA administration (150 mg/kg/daily) increased the number of NeuN+ postmitotic neurons and TH+ DA neurons in the grafts. Furthermore, VPA (150 mg/kg/daily) and ZNS (30 mg/kg/daily) increased the number of TH+FOXA2+ midbrain DA neurons. These results suggest that the systemic administration of VPA and ZNS may improve the efficiency of cell replacement therapy using iPSCs to treat PD.